DOI: 10.29007/8jkt
|View full text |Cite
|
Sign up to set email alerts
|

DFS ADS-B Implementation in High Density Radar Controlled Airspace – Experiences and Challenges

Abstract: The German Air Navigation Service Provider (ANSP) DFS Deutsche Flugsicherung (DFS) is operating a surveillance infrastructure mainly based on radars and multilateration systems, which provides surveillance information and receives aircraft derived data. The implementation and use of the new surveillance technology Automatic Dependent Surveillance – Broadcast (ADS-B) has to provide benefits in terms of safety, performance or costs. DFS operations require a permanent double surveillance coverage for the area of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 0 publications
1
5
0
Order By: Relevance
“…The wider gap in heating load in the single-glazed house is due to the nonlinear effect mentioned in section 4. 13. The fact that the heating load increases even though the solar gain does as well, confirms the common knowledge that the higher losses from the single-glazed windows are dominant.…”
Section: Single Glazingsupporting
confidence: 68%
See 2 more Smart Citations
“…The wider gap in heating load in the single-glazed house is due to the nonlinear effect mentioned in section 4. 13. The fact that the heating load increases even though the solar gain does as well, confirms the common knowledge that the higher losses from the single-glazed windows are dominant.…”
Section: Single Glazingsupporting
confidence: 68%
“…This program was chosen since it has been extensively tested and used in modelling passive solar houses(5.6), in comparison with other detailed simulations and design methods (7) including BREDEM-S(8.9). SERI-RES has also been checked against results obtained with the program ESp_r (12,13) in modellin a passive solar test cell in the EC-PASSYS program (10)(11)(12)(13) . Some calculations were performed with the UK program APACHE, available from IES, Glasgow.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…implementation onto the existing systems called multilateration (MLAT) [5], [39]- [45] is possible without any significant change, and ideally, with only a software upgrade of the central processor. This is of benefit for air navigation service providers.…”
Section: Introductionmentioning
confidence: 99%
“…A study of uncertainties in aircraft noise calculations determined standard uncertainties of 133 m (436 ft) laterally and of 27 m (89 ft) vertically for radar data in Switzerland [5]. A study by the German Air Navigation Service Provider (ANSP) showed that ADS-B data are generally subject to smaller uncertainties than radar data, but present the challenge that the uncertainties are created by the on-board sensors of the aircraft rather than by an on-ground detection [6]. Thus ADS-B data quality varies between aircraft.…”
Section: Introductionmentioning
confidence: 99%